Assessment of contamination source and quality control approach for polycyclic aromatic hydrocarbons in wood-pressed rapeseed oil. Issue 6 (3rd June 2018) - Liu, Ruijie; Zhang, Youfeng; Wang, Jun; Pan, Qiqi; Luo, Yingqi; Sun, Yujie; Jin, Qingzhe; Wang, Xingguo
ABSTRACT: Contamination sources of polycyclic aromatic hydrocarbons (PAHs) in the raw material, oil production and storage processes of wood-pressed rapeseed oil were investigated in this study. The results showed that benzo[ a ]pyrene (BaP) and PAH4 (sum of BaP, benzo[ a ]fluoranthene, benzo[ b ]fluoranthene and chrysene) were unevenly distributed in the kernel (0.56–0.98 and 2.84–8.64 μg/kg, respectively) and hull (1.53–3.17 and 13.49–22.31 μg/kg, respectively) of the rapeseed raw materials. The contents of BaP and PAH4 continuously increased during the process of wood-pressed rapeseed oil, ranging from 2.21 to 10.93 and 9.36 to 40.03 μg/kg, thus demonstrating that a wide range of pollution sources of PAHs existed for the test wood-pressed rapeseed oils. The initial temperature and time of roasting should be controlled at <210°C and <60 min, due to the generation of PAHs in rapeseed by over-roasting. In addition, contact tools and substance such as lubricating oil (from the mill), heat-transfer oil (from roasting machine), rubber gaskets and straws should be properly screened. The BaP and PAH4 of rapeseed placed in the roasting area increased from 0.5 to 2.24 and from 2.08 to 9.03 μg/kg, respectively. Therefore, roasting fume control and treatment systems are necessary and the roasting section should be strictly isolated from the other stages. Storage can slightly lower the PAHs amounts in the rapeseed oil, which made the contents of BaP and PAH4 decrease from 27.00 to 24.70 and from 138.63 to 117.58 μg/kg, respectively. Quality control measures of PAHs in wood-pressed rapeseed oil were proposed and implemented, and the final oil products' BaP and PAH4 were kept below 2 and 10 μg/kg, respectively, which meets the European Commission Regulation No. 835/2011.